The Effects of lower-body plyometric program on the lunge distance of collegiate level fencers - Romey, Vincent Vaughan M. 1998-; Papa, Emmanuel Liberato V. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
The study aims to evaluate the effects of a lower-body plyometric program on the distance of the lunge of collegiate level fencers. Studies suggest that plyometrics is a good way to help increase the lunge. The researcher believes that after the intervention a subject will be able to self-optimize to a greater extent. The researcher will test the anthropometry of the leg span of subjects, for body-scaled affordance. With fencers instead of using a vertical test, the researcher will be using a horizontal jump test instead, specifically the standing broad jump and the horizontal squat jump. The horizontal jumping ability will be correlated to the lunge because it is a better indicator rather than the vertical jumping ability. Here, action-scaled affordance will come to play, where the subject's capability for a certain test will be tested. Another test will be the lunge distance test, also for the action-scaled affordance theory. The intervention will consist of 11 subjects that will be assigned to a control and experimental group. The tests include a lunge distance test, leg length anthropometry, standing long, jump, and a horizontal squat jump.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Plyometrics; Exercise -- Physiological aspects; Fencing -- Training